Local earthquake tomography of the Larderello-Travale geothermal field. (January 2020) - Bagagli, M.; Kissling, E.; Piccinini, D.; Saccorotti, G.
Highlights: New P-wave velocity model for the geothermal area of Larderello-Travale (Italy) from local earthquake tomography. Identification of a low-velocity anomaly at shallow depths (≈7 km) likely related to partially-molten granites. The rock volume containing the productive horizon displays P-wave velocity values between 5 and 5.5 km s −1 . Abstract: The Larderello-Travale Geothermal Field in South-West Tuscany (Italy) is the oldest and among the most productive geothermal fields in the world. A new 3D model of seismic P-wave velocity ( V P ) of the upper crust beneath the geothermal field is derived by inverting a set of highly consistent travel-times from local-earthquakes. Results document a marked correlation of V P with previously described, high-reflectivity horizons. We also determined a low velocity body ( V P ∼5 km s −1 ) culminating at depths of about 7 km, with estimated volume of 35–40 km 3 . Such low velocities are consistent with a granite at temperatures above 700 °C, thus in a partially-molten status.